C-Band Monopulse Planar Array and Feeding Network - Perotoni,Marcelo B. (2021)
Abstract Monopulse radars operate with simultaneous beams and are used for tracking purposes, relying only on hardware to provide a real-time indication of the target position. A monopulse array and its feeding network is implemented and tested, in the frequency of 5.4 GHz, based on patch antennas using dieletric to provide wide bandwidth and high gain. The system field styrofoam as pattern was evaluated in two different environments, a shielded room and an indoor area. Results agreed with simulation for either individual elements as well as the final integrated monopulse array.